A conceptual study of imaging system for 1U cubesat application / Fatimah Zaharah Ali ... [et al.] - Ali, Fatimah Zaharah; Maskey, Abhas; Ahmad Thaheer, Ahmad Shaqeer; Wan Chek, Wan Ahmad Khusairi; Jusoh, Mohamad Huzaimy (Universiti Teknologi MARA, 2021)
1U CubeSat has limitations in mechanical and electrical properties that pose restriction in selecting imaging sensor for camera mission. As a result, 1U CubeSat usually carries unfavorable-performance imaging system that delivers low quality of imagery in terms of resolution and other traits. As 1U CubeSat is mostly suitable for small satellite projects due to shorter development time and cheaper production cost, it is imperatively useful if the 1U CubeSat can provide high quality imaging system similar to the camera mission provided by 3U or larger CubeSats which come with longer development time and greater production cost. In this paper, a conceptual study on designing an imaging system with optimal attributes and performance for 1U-sized CubeSat will be discussed. The parameter to be examined for performance improvement is the ground sampling distance (GSD) which is associated with the application of the focal length. The study uses the quantitative measurements as a validation tool to prove the correlation between focal length of the selected lens and the GSD. Moreover, it can also be used to identify the appropriate type of protocol interface to be used that will affect overall performance of the imaging system This conceptual study will provide new guideline in designing a high performance imaging system for small type of satellite, where it will complement the conventional method of selecting the imagery.